Effect of neck strength training on health-related quality of life in females with chronic neck pain: a randomized controlled 1-year follow-up study - Salo, Petri K; Häkkinen, Arja H; Kautiainen, Hannu; Ylinen, Jari J (Health and quality of life outcomes, 2010)
Background Chronic neck pain is a common condition associated not only with a decrease in neck muscle strength, but also with decrease in health-related quality of life (HRQoL). While neck strength training has been shown to be effective in improving neck muscle strength and reducing neck pain, HRQoL among patients with neck pain has been reported as an outcome in only two short-term exercise intervention studies. Thus, reports on the influence of a long-term neck strength training intervention on HRQoL among patients with chronic neck pain have been lacking. This study reports the effect of one-year neck strength training on HRQoL in females with chronic neck pain. Methods One hundred eighty female office workers, 25 to 53 years of age, with chronic neck pain were randomized to a strength training group (STG, n = 60), endurance training group (ETG, n = 60) or control group (CG, n = 60). The STG performed high-intensity isometric neck strengthening exercises with an elastic band while the ETG performed lighter dynamic neck muscle training. The CG received a single session of guidance on stretching exercises. HRQoL was assessed using the generic 15D questionnaire at baseline and after 12 months. Statistical comparisons among the groups were performed using bootstrap-type analysis of covariance (ANCOVA) with baseline values as covariates. Effect sizes were calculated using the Cohen method for paired samples. Results Training led to statistically significant improvement in the 15D total scores for both training groups, whereas no changes occurred for the control group (P = 0.012, between groups). The STG improved significantly in five of 15 dimensions, while the ETG improved significantly in two dimensions. Effect size (and 95% confidence intervals) for the 15D total score was 0.39 (0.13 to 0.72) for the STG, 0.37 (0.08 to 0.67) for the ETG, and -0.06 (-0.25 to 0.15) for the CG. Conclusions One year of either strength or endurance training seemed to moderately enhance the HRQoL. Neck and upper body training can be recommended to improve HRQoL of females with neck pain if they are motivated for long-term regular exercise. Trial Registration ClinicalTrials.gov NCT01057836